2012
DOI: 10.1590/s0100-879x2011007500152
|View full text |Cite
|
Sign up to set email alerts
|

MMP-1/PAR-1 signal transduction axis and its prognostic impact in esophageal squamous cell carcinoma

Abstract: The matrix metalloprotease-1 (MMP-1)/protease-activated receptor-1 (PAR-1) signal transduction axis plays an important role in tumorigenesis. To explore the expression and prognostic value of MMP-1 and PAR-1 in esophageal squamous cell carcinoma (ESCC), we evaluated the expression of two proteins in resected specimens from 85 patients with ESCC by immunohistochemistry. Sixty-two (72.9%) and 58 (68.2%) tumors were MMP-1- and PAR-1-positive, respectively, while no significant staining was observed in normal esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…According to our data in this study, MMP-1 and PAR-1 were both overexpressed in NPC tissues, which is consistent with the previous studies of Ben Nasr et al19 and Zhu et al30 Interestingly, the expression levels of MMP-1 in the NPC specimens were significantly correlated with those of PAR-1, suggesting a regulatory relationship between MMP-1 and PAR-1. In addition, we found that MMP-1 and/or PAR-1 expression levels were all associated with aggressive tumor progression and poor overall survival of the NPC patients, which is also similar with the previous findings in other cancers 2224. More importantly, the multivariate analyses here showed that the combined MMP-1 and PAR-1 overexpression was an independent prognostic factor for overall survival ( P = 0.001) in NPC patients, but the upregulation of MMP-1 and PAR-1 alone was, in each case, not an independent prognostic factors for this disease, suggesting the importance of the interaction between MMP-1 and PAR-1 in the clinical outcome of NPC patients.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to our data in this study, MMP-1 and PAR-1 were both overexpressed in NPC tissues, which is consistent with the previous studies of Ben Nasr et al19 and Zhu et al30 Interestingly, the expression levels of MMP-1 in the NPC specimens were significantly correlated with those of PAR-1, suggesting a regulatory relationship between MMP-1 and PAR-1. In addition, we found that MMP-1 and/or PAR-1 expression levels were all associated with aggressive tumor progression and poor overall survival of the NPC patients, which is also similar with the previous findings in other cancers 2224. More importantly, the multivariate analyses here showed that the combined MMP-1 and PAR-1 overexpression was an independent prognostic factor for overall survival ( P = 0.001) in NPC patients, but the upregulation of MMP-1 and PAR-1 alone was, in each case, not an independent prognostic factors for this disease, suggesting the importance of the interaction between MMP-1 and PAR-1 in the clinical outcome of NPC patients.…”
Section: Discussionsupporting
confidence: 90%
“…PAR-1 expression has been similarly demonstrated to correlate with tumor progression both in vitro and in vivo. In light of the potential significance of MMP-1 and PAR-1 in the tumorigenesis and tumor progression of various cancers, accumulating studies2224 have been performed to investigate the role of the MMP-1/PAR-1 axis in cancers. For example, the blockage of the MMP-1/PAR-1 interaction by a monoclonal antibody against PAR-1 has been shown to significantly reduce the migration ability of human mesenchymal stem cells 35.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…also reported that the PAR1 pathway can be activated by conditioned medium containing MMP-1 secreted by tumor cells (38). Furthermore, in a number of recent clinical studies MMP-1 and PAR1 co-expression or co-localization in tumor tissues positively correlated with poor prognosis or unfavorable outcome for three different types of human carcinomas (39-41). …”
Section: Discussionmentioning
confidence: 99%